2021
DOI: 10.1101/2021.05.23.445307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Spatiotemporal Map of Reading Aloud

Abstract: Reading words aloud is a foundational aspect of the acquisition of literacy. The rapid rate at which multiple distributed neural substrates are engaged in this process can only be probed via techniques with high spatiotemporal resolution. We used direct intracranial recordings in a large cohort to create a holistic yet fine-grained map of word processing, enabling us to derive the spatiotemporal neural codes of multiple word attributes critical to reading: lexicality, word frequency and orthographic neighborho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…meech) presented in lower-case Arial font, 150 pixels high (∼2.2° visual angle) ( Fig. 1A ) ( Woolnough et al, 2021a ). Stimuli were presented using Psychophysics Toolbox ( Kleiner et al, 2007 ) run in Matlab.…”
Section: Methodsmentioning
confidence: 99%
“…meech) presented in lower-case Arial font, 150 pixels high (∼2.2° visual angle) ( Fig. 1A ) ( Woolnough et al, 2021a ). Stimuli were presented using Psychophysics Toolbox ( Kleiner et al, 2007 ) run in Matlab.…”
Section: Methodsmentioning
confidence: 99%
“…dream) and pseudowords (e.g. meech) presented in lower-case Arial font, 150 pixels high (~2.2° visual angle) (Figure 1A) (Woolnough et al, 2021a). Stimuli were presented using Psychophysics Toolbox (Kleiner et al, 2007) run in Matlab.…”
Section: Methodsmentioning
confidence: 99%
“…PLV statistics were performed using a bootstrapped null distribution, randomly re-pairing trials between electrodes, using 5,000 repetitions. Phase probability distributions were quantified, using 30 equally spaced bins between -π and π, and mutual information (MI) was calculated based on these distributions at each time point, 1A) (Woolnough et al, 2021a). Stimuli were presented using Psychophysics Toolbox (Kleiner et al, 2007) run in Matlab.…”
Section: Methodsmentioning
confidence: 99%
“…Previous intracranial work identified distinct fronto-temporal networks for sentence reading, sensitive to sentence-and lexical-level meaning, respectively (Woolnough et al, 2023). Research on aphasic patients suggested that left hemispheric fronto-temporal language regions are selectively engaged in language by storing domain-specific knowledge representations, whereas nonlinguistic abilities do not rely on the language system (Fedorenko & Varley, 2016).…”
Section: Introductionmentioning
confidence: 99%